Germination of Ceiba speciosa seeds collected in Altitude Brejo - Silva, João Henrique Constantino Sales; Azeredo, Gilvaneide Alves de; Targino, Vitor Araujo; Costa, Paulo Marks de Araújo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Ceiba speciosa (A. St.-Hil.) Ravenna (Malvaceae) is a tree species native to Brazilian forests, indicated in the restoration of degraded areas and in the upholstery industry. This work aimed to verify substrates and temperatures favorable to the germination of paineira seeds collected in a forest remnant of Altitude Brejo in Paraíba. The experimental design used was completely randomized, in a 2 × 4 factorial arrangement, consisting of combinations of two temperatures (25 and 30 ºC) and four substrates (sand, vermiculite, earth and “mata-borrão” paper), with four replications of 25 seeds each. The following characteristics were analyzed: water content (%) of seeds, emergence percentage, average emergence time, percentage of normal seedlings and emergence speed index (ESI). There was a significant effect on the temperature × substrate interaction for all variables, except ESI. Vermiculite and sand substrates at a constant temperature of 25 °C are recommended for conducting seed germination tests of Ceiba speciosa. The temperature of 30 °C can be indicated when associated with the vermiculite substrate. The substrate on “mata-borrão” paper is not indicted for the germination of seeds of this species. A study with seeds from different populations of this species is suggested to confirm the influence of the seed's origin on its germinative performance when subjected to associated environmental factors, such as temperatures and substrates.